A Lyre on the Ground - Almazova, Nina (Hyperboreus, 2013)
On an Attic stemmed plate a dancing girl approaches a chelys-lyre that lies on the ground, whereas the inscription ΧΟΡΦΕΛΕΣ indicates a chorus performance. In Classical Athens, a maidens’ chorus seems only thinkable on religious occasions (the paper lists known cases of Athenian women dancing and singing at the cult ceremonies). Lyres lying on the ground (in outdoor scenes), as well as instruments hanging on the wall, cannot be interpreted as producing sounds. Therefore in the image under consideration, although the dance has already begun, the lyre does not sound yet – and this needs an explanation. There is evidence that the choruses were accompanied both by stringed and wind-instruments, sometimes in turns. Therefore I suggest that the girl is ﬁnishing a dance while being accompanied by an aulos and is hurrying to pick up the lyre to accompany the second part of the performance. For a number of choes with a lyre on the ground and dancing or running ﬁgures nearby the same interpretation is possible, but it is not necessary, since we can interpret them as simple merry-making or as school competitions. The intended purpose of depicting a lyre on the ground may be various, but an explanation, which does not suggest that an instrument played by no one implies the music that accompanies the scene, is always possible. In the Classical period, symbolic meaning of a lyre is still inseparable from its actual use.